Determination of the Beginning of the Hijri Month by Tarekat Asy-Syahadatain in Cirebon Regency - Rizal Ramadhan; Ahmad Izzuddin; Muhammad Arif Royyani (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2025)
The Asy-Syahadatain tarekat in Cirebon Regency not only conducts various religious activities but also has its own system for determining the beginning of the Hijri months, which often differs from the government's official determination. This study is a qualitative field research conducted in the villages of Munjul and Panguragan Wetan. Primary data were collected through interviews with religious scholars and prominent figures of the tarekat, while secondary data included the Isnaeniyah calendar, Asy-Syahadatain calendar, and the results of the rukyatul istitar observation at Kejawanan Beach. The research findings indicate that this tarekat uses the Isnaeniyah hisab method, the Asy-Syahadatain calendar, which is adopted from the Kudus calendar, as well as the rukyat istitar system. Although there are differences in methods, some followers are still allowed to follow the government’s determination. No conflict arises among followers due to the strong emotional bond they share with their respective Kiais. Each Kiai leads their own study group and provides an explanation of the methodology before determining the start of Ramadan, Shawwal, or Dhu al-Hijjah. This closeness and trust are the main factors behind the followers’ obedience to each Kiai’s decisions.